Go tell it on the mountain - Baldwin, James, 1924-1987 (Modern library of the world's best books., 1995)
"Mountain," Baldwin said, "is the book I had to write if I was ever going to write anything else." Go Tell It On The Mountain, first published in 1953, is Baldwin's first major work, a novel that has established itself as an American classic. With lyrical precision, psychological directness, resonating symbolic power, and a rage that is at once unrelenting and compassionate, Baldwin chronicles a fourteen-year-old boy's discovery of the terms of his identity as the stepson of the minister of a storefront Pentecostal church in Harlem one Saturday in March of 1935. Baldwin's rendering of his protagonist's spiritual, sexual, and moral struggle of self-invention opened new possibilities in the American language and in the way Americans understand themselves.